Counterproductive work behaviour, organisational justice, organisational embeddedness and psychological ownership among police force in Pakistan - Mehmood, Sultan Adal (2019)
Counterproductive work behaviour (CWB) is commonplace in organisations. The consequences of such behaviour have been proven inimical for organisations and their stakeholders. The police force is considered a vital state institution; but, the presence of CWB among police employees is very rampant especially in underdeveloped countries such as Pakistan. Organisational justice (OJ) is regarded as a prime determinant of CWB. Although numerous researchers have studied the relation of OJ and CWB, none of them have explored the role of organisational embeddedness (OE) and psychological ownership (PO) in this regard. This study thus aimed to investigate the mechanisms through which OJ is translated into CWB among the police in Pakistan. Such relationship is explained through a moderated mediation model where organisational embeddedness mediates between OJ and CWB, and PO moderates the relationship between OE and CWB. The COR theory was used as the underpinning theory to explain the interrelationships among the constructs.